2021
DOI: 10.3390/jcdd8110144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early and Delayed Commencement of Paricalcitol in Combination with Enalapril on the Progression of Experimental Polycystic Kidney Disease

Abstract: Vitamin D secosteroids are intranuclear regulators of cellular growth and suppress the renin-angiotensin system. The aim of this study was to test the hypothesis that the vitamin D receptor agonist, paricalcitol (PC), either alone or with enalapril (E) (an angiotensin-converting enzyme inhibitor), reduces the progression of polycystic kidney disease. Preventative treatment of Lewis polycystic kidney (LPK) and Lewis control rats with PC (0.2 μg/kg i.p. 5 days/week) or vehicle from postnatal weeks 3 to 10 did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A clinical trial of niacinamide (vitamin B) in patients with ADPKD showed no significant differences in primary outcomes 58 while studies on the effects of vitamin D and vitamin E have produced mixed results. [59][60][61] Supplements without Human Data in Patients with ADPKD BHB Given the potential benefits of ketogenic diet and challenges of long-term adherence, BHB combined with other supplements, such as citrate, have been developed. The safety and efficacy of these supplements have not been assessed or validated in patients with ADPKD.…”
Section: Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical trial of niacinamide (vitamin B) in patients with ADPKD showed no significant differences in primary outcomes 58 while studies on the effects of vitamin D and vitamin E have produced mixed results. [59][60][61] Supplements without Human Data in Patients with ADPKD BHB Given the potential benefits of ketogenic diet and challenges of long-term adherence, BHB combined with other supplements, such as citrate, have been developed. The safety and efficacy of these supplements have not been assessed or validated in patients with ADPKD.…”
Section: Vitaminsmentioning
confidence: 99%
“…A clinical trial of niacinamide (vitamin B) in patients with ADPKD showed no significant differences in primary outcomes 58 while studies on the effects of vitamin D and vitamin E have produced mixed results. 5961…”
Section: Overview Of Nutritional Supplementationmentioning
confidence: 99%